A deprotection procedure using SO3H silica gel to remove non-silyl protecting groups. Issue 2 (17th January 2019) - Karaki, Fumika; Kuwada, Miki; Tajiri, Saki; Kanda, Misaki; Yanai, Mari; Kamimura, Mitsuhiro; Itoh, Kennosuke; Fujii, Hideaki
Abstract: Protecting groups are indispensable in organic synthesis and there is a great need for a variety of deprotection methods. Here, we investigated the scope of the application of a deprotection procedure using SO3 H silica gel, which we have previously reported as a desilylation procedure. Under these conditions, -OMOM, -OSEM, -OTHP, and -OAc groups and dimethyl acetal were cleaved. Pivaloyloxy, benzyloxy and methoxy carbonyl groups remained intact and selective deprotection of TBS groups in the presence of other protecting groups was accomplished. We succeeded in cleaving an acetyl group on a secondary alcohol in a highly polar nortropine derivative. Our findings here provide another deprotection option and would be helpful in the synthesis of multifunctional compounds. Graphical Abstract: